Statistical Methods in Biology Design and Analysis of Experiments and Regression - Welham, Suzanne Jane Gezan, S.A (CRC Press, 2015)
"Written in simple language with relevant examples, this illustrative introductory book presents best practices in experimental design and simple data analysis. Taking a practical and intuitive approach, it only uses mathematical formulae to formalize the methods where necessary and appropriate. The text features extended discussions of examples that include real data sets arising from research. The authors analyze